An early start to foreign language literacy in English primary school classrooms. Issue 5 (2nd September 2020) - Porter, Alison
ABSTRACT: This study investigated the systematic and principled teaching of foreign language (FL) literacy in two young learner classrooms in England. Over the course of 23 weeks, two classes of 9–11 year olds ( N = 45) learned spoken and written language through an integrated pedagogy. The underpinning rationale was to explore principled ways of teaching FL literacy to young beginner learners. The study also set out to document the nature of linguistic progression and potential attrition in primary school foreign language classrooms through measuring a range of FL outcomes: receptive vocabulary and elicited imitation (general proficiency); reading aloud and reading comprehension (literacy). It was found that 45 the participants made slow but statistically significant and long-term progress, the latter evidenced by limited attrition, across both FL general proficiency and FL literacy constructs. Qualitative data showed that children enjoyed aspects of literacy instruction and opportunities to experiment with FL use. Findings have the potential to inform young FL learning empirical and pedagogic evidence, particularly relating to the teaching and learning of FL literacy in primary school settings.